The Prediction of Professional Success in Apprenticeship: The Role of Cognitive and Non-Cognitive Abilities, of Interests and Personality - Diedrich, Jennifer; Neubauer, Aljoscha C.; Ortner, Anna (International Journal for Research in Vocational Education and Training, 2018)
Context: We addressed the issue of person-job-fit by focussing on both professional success and work satisfaction. Publications studying the predictive validity of (cognitive) ability, personality, or vocational interest alone have shown relationships with professional success or work satisfaction for each predictor separately. Nevertheless, these predictors have rarely been studied simultaneously. Methods: To this end we tested the incremental validity of abilities, traits, and interests in a sample from diverse occupations: In 648 apprentices and students from five different branches (Food, Tech, People, Office, Craft) the (incremental) contributions of 3 intelligence factors (verbal, numerical, spatial), 3 alternative abilities (social-emotional, creative, practical), 4 conscientiousness facets, other big five factors (O, E, A, N), and of 14 professional interests were analysed regarding prediction of GPA in professional schools and school/job satisfaction. Results: Intelligence and conscientiousness were best predictors, followed by social-emotional competence and interests, whereas other traits provided marginal contributions. Predictors varied between branches, mostly following expectations. The test battery allowed a very good prediction of apprenticeship success (max. 37%), but for some branches prediction was considerably lower. Conclusion: Criteria for person-job-fit are not swappable, neither are the predictors. Professional success was mostly predicted by a different predictor set -namely ability and the personality dimension of conscientiousness- then satisfaction, which was mostly predicted by non-interest in a certain occupation. As a practical implication, we conclude that choosing the right candidate for a certain branch one needs to use a broad set of predictor variables. Besides cognitive ability also personality and vocational interests had predictive validity for an individuals person-job-fit.